The Effect of Implementing PBL, DL And DI on Critical Thinking Ability Mathematics Reviewed from Motivation to Learn - Nazipurahman, Muhammad; Syaiful, Syaiful; Maizon, Maizon (Journal of Educational Sciences, 2025)
This study aims to improve students' mathematical critical thinking skills by enhancing their intrinsic motivation to learn. It compares the effects of three instructional models PBL (Problem Based Learning), DL (Discovery Learning), and Direct Instruction (DI) on students’ mathematical critical thinking across four levels of intrinsic motivation: high, medium, low, and overall. The research employed a quasi-experimental design with a non-equivalent control group. The sample consisted of 75 seventh-grade students: 25 students each from classes VII A and VII B as experimental groups using PBL and DL models, and 25 students from class VII C as the control group using DI. Data were analyzed using two-way ANOVA. Results indicate that PBL significantly outperforms DL in improving students’ mathematical critical thinking skills. In turn, DL shows a more pronounced effect compared to DI. Intrinsic motivation plays a crucial role: students with high and medium levels of motivation benefit the most, while those with low motivation show weaker outcomes. A significant interaction effect was found between the type of instructional model and the level of intrinsic motivation, suggesting that the choice of instructional model should consider students' motivational profiles. These findings imply that instructional strategies tailored to students' motivation levels can significantly enhance mathematical critical thinking abilities.